Diffusion-weighted MR imaging using FASE sequence for 3T MR system: Preliminary comparison of capability for N-stage assessment by means of diffusion-weighted MR imaging using EPI sequence, STIR FASE imaging and FDG PET/CT for non-small cell lung cancer patients. Issue 11 (November 2015) - Ohno, Yoshiharu; Koyama, Hisanobu; Yoshikawa, Takeshi; Takenaka, Daisuke; Kassai, Yoshimori; Yui, Masao; Matsumoto, Sumiaki; Sugimura, Kazuro
Highlights: On DWI, FASE sequence has better image quality and diagnostic performance than EPI sequence. DWI with FASE sequence as well as STIR FASE imaging have better potential for lymph node metastasis assessment than DWI with EPI sequenece and PET/CT on per node basis analysis. On N-stage assessment, DWI with FASE sequence as well as STIR FASE imaging have higher capabilty than DWI wth EPI sequence and PET/CTin NSCLC patients. Abstract: Purpose: To prospectively compare the diagnostic capability of diffusion-weighted MR imaging obtained with fast advantage spin-echo sequence (FASE-DWI) and echo planar imaging sequence (EPI-DWI), short inversion time inversion recovery fast advanced spin-echo (STIR FASE) imaging and FDG PET/CT for N-stage assessment of non-small cell carcinoma (NSCLC) patients. Materials and methods: 95 consecutive operable NSCLC patients underwent STIR FASE imaging, FASE-DWI and EPI-DWI with a 3T system, integrated PET/CT, surgical treatment and pathological and follow-up examinations. Probability of lymph node metastasis was visually assessed using a 5-point visual scoring system. ROC analyses were used to compare diagnostic capability of all methods, while their diagnostic performance was also compared by means of McNemar's test on a per node basis. Finally, McNemar's test was also used for statistical comparison of accuracy of N-stage assessment. Results: Areas under the curve (Azs) for STIR FASE imaging (Az = 0.95) and FASE-DWI (Az = 0.92) were significantly larger than those for EPI-DWI (Az = 0.78; p  < 0.0001 for STIR FSE imaging and FASE-DWI) and PET/CT (Az = 0.85; p  = 0.0001 for STIR FSE imaging, p  = 0.03 for FASE-DWI) on a per node basis analysis. Accuracy of N-stage assessment using STIR FASE imaging (84.2% [80/95]) and FASE-DWI (83.2% [79/95]) was significantly higher than that using EPI-DWI (76.8% [73/95]; p  = 0.02 for STIR FASE imaging, p  = 0.03 for FASE-DWI) and PET/CT (73.7% [70/95]; p  = 0.002 for STIR FSE imaging, p  = 0.004 for FASE-DWI). Conclusion: Qualitative N-stage assessments of NSCLC patients obtained with FASE-DWI as well as STIR FASE imaging are more sensitive and/or accurate than those obtained with EPI-DWI and FDG PET/CT.